Differences in plasma metabolites related to Alzheimer's disease, APOE ε4 status, and ethnicity - Vardarajan, Badri (Alzheimers Dement (N Y), 2020)
INTRODUCTION: We investigated metabolites in plasma to capture systemic biochemical changes associated with Alzheimer's disease (AD). METHODS: Metabolites in plasma were measured in 59 AD cases and 60 healthy participants of African American (AA), Caribbean Hispanic (CH), and non‐Hispanic white (NHW) ancestry using untargeted liquid‐chromatography–based ultra‐high‐resolution mass spectrometry. Metabolite differences between AD and healthy, ethnic groups and apolipoprotein E gene (APOE) ε4 status were analyzed. Untargeted network analysis identified pathways enriched in AD‐associated metabolites. RESULTS: A total of 5929 annotated metabolites were measured. Partial least squares discriminant analysis (PLS‐DA) inferred that AD clustered separately from healthy controls (area under the curve [AUC] = 0.9816); discriminating pathways included glycerophospholipid, sphingolipid, and non‐essential amino acid (alanine, aspartate, glutamate) metabolism. Metabolic features in AA clustered differently from CH and NHW (AUC = 0.9275), and differed between APOE ε4 carriers and non‐carriers (AUC = 0.9972). DISCUSSION: Metabolites, specifically lipids, were associated with AD, APOE ε4, and ethnic group. Metabolite profiling can identify perturbed AD pathways, but genetic and ancestral background need to be considered.